Immunohistochemical Evaluation of EGFR Expression in Oral Dysplastic and Non-Dysplastic Leukoplakia - Nasrollah Saghravanian; Narges Ghazi; Abdollah Javan rashid; Mohammad Ebrahimi (Mashhad University of Medical Sciences, 2023)
Background: This study aimed to evaluate the expression of epidermal growth factor receptor (EGFR) in oral leukoplakia with and without dysplasia and normal mucosa by immunohistochemistry.Materials and Methods: In this study, 45 samples of oral leukoplakia with and without dysplasia of normal mucosa (15 samples per group) were selected from the archives of the oral and maxillofacial pathology department Mashhad dental school. Immunohistochemical evaluation of EGFR expression according to the manufacturer's instructions was performed. The percentage of immunoreactivity was recorded and compared by statistical tests (Chi-square One-way ANOVA Kruskal-WallisMann-Whitney U). Results: There was a statistically significant difference among the three groups with regards to EFGR expression (P=0.001). Increased expression of EGFR from normal mucosa to non-dysplastic leukoplakia and dysplastic leukoplakia was observed. There was no statistically significant difference between dysplastic and non-dysplastic leukoplakia.Conclusion: Increased expression of EGFR was recognized as a key contributing factor for malignant transformations from normal mocusa to non-dysplastic and dysplastic leukoplakia, therefore indicating its role in the carcinogenesis of oral mucosa.